A Quantitative and Qualitative Study of User Experience Impact on Mobile Game: Preliminary Study - Audrey Steccy anak Douglas, Aslina Baharum, Suhaida Halamy, Dian Darina Indah Daruis, Emelia Abdul Rahim, Noorsidi Aizuddin Mat Noor (International Journal of Advanced Science and Technology, 2020)
This paper presents the effect of great user experience on mobile games. Human-Computer Interaction (HCI) is about the interaction between computer interfaces and humans. In the world of HCI, user experience is one of the common key terms known by all HCI researchers. In HCI, user experience plays an important part to evaluate the user experience design since it is one of the HCI branches that focus interaction of products. The definition of user experience is a degree of positive or a negative emotion that is specific for the user who is experienced in a specific context during and after product use and that motivates for further usage. The goals of this research are to identify the user expectation or experience while playing mobile games and also to examine the triggering context and its regularities with core experience. The method used is mixed methods (qualitative and quantitative) using five participants; consists of an expert mobile gamer, three intermediate mobile gamers and a beginner mobile gamer. Results show that design and development should consider the user’s expectation, to allow the game to achieve its purpose and can influence the users’ mood to play mobile game.